Promoting fruit and vegetable intake in urban Ethiopia: An experiment using video-based communication - Abate, Gashaw T.; Baye, Kaleab; de Brauw, Alan; Hirvonen, Kalle (International Food Policy Research Institute, 2019)
This pilot experiment aims to address the knowledge gaps on the nutrition and health benefits of fruits and vegetables to help find ways to increase both consumption frequency and amounts at the house-hold level. While there are already commendable efforts in the country to improve overall nutrition knowledge through behavioral change communication, so far, the interventions focus on rural areas and are limited to conveying recommended behaviors with little or no emphasis on the mechanisms by which diet quality can improve nutrition and health outcomes. This experiment will be the first of its kind to introduce systematic nutrition behavioral change communication in urban Ethiopia with an enhanced intervention to communicate the mechanisms through which the consumption of fruits and vegetables can lead to better nutrition and health outcomes.